Aesthetic Politics in Fashion - Gaugele, Elke (Publication Series of the Academy of Fine Arts Vienna, 2014)
Aesthetic Politics in Fashion outlines critical studies in the present cross-sections of fashion, art, politics, and global capitalism. Critically examining contemporary collaborations of artists, media, and fashion labels, this groundbreaking anthology locates fashion within ecological and ethical discourses, postcolonial styles, and critical reflections on whiteness. Contributions from a distinguished group of international scholars debate fashion as a cultural phenomenon at the intersection of artistic, creative, economic, and everyday practices. Aesthetic economies, the production of space, and alternative aesthetic politics are explored from interdisciplinary angles: art history, cultural science, sociology, design, and fashion studies. Aesthetic Politics in Fashion advances theorizing of fashion as an aesthetic metapolitics.